Reducing Infectious Complications Following Transrectal Ultrasound-guided Prostate Biopsy: A Systematic Review - Walker, Jordon T. (Rev Urol, 2016)
A rise in antimicrobial resistant uropathogens has generated a global increase in infections following transrectal ultrasound-guided prostate biopsy (TRUS-Bx). We performed a systematic search of Ovid MEDLINE® and PubMed to comprehensively review strategies to mitigate infections. Of 1664 articles retrieved, 62 were included. The data suggest that augmented prophylaxis and povidone-iodine bowel preparation warrant consideration in regions with high rates of antimicrobial resistance. Transperineal biopsy may be a safer, equally effective alternative to TRUS-Bx in select cases. Recent international travel appears to increase patients’ risk for experiencing infections. These findings can aid clinicians in minimizing post-TRUS-Bx infectious complications.